Solid Waste Management and Disaster Preparedness of At-Risk Municipalities of Zamboanga Del Norte - Mansanadez, Evangeline (JPAIR Multidisciplinary Research, 2019)
The by-product of every human activity is waste. The government initiative of "Tapat ko, linis ko" and "Basura ko, tapon ko" calls for every Filipino to be responsible for managing their solid wastes to prevent disaster properly. This survey aimed to determine the solid waste management and disaster preparedness of at-risk municipalities of Zamboanga del Norte. A descriptive method of research using a questionnaire-checklist was employed to the respondents who were considered by the purposive sampling technique. Data gathered were treated using a frequency count. Findings revealed that household waste makes up the largest bulk of waste. The majority of households have compost pit dug in the backyards as a dumping site, while government sites were used as open dumping areas of wastes generated from business establishments and offices operating in the town commercial areas. The conduct of regular monitoring of garbage disposal, checking of municipal dump site condition, and unclogging of canals littered with dumped garbage is the common solid waste management practices and flash floods disaster preparedness. Their LDRRMC team and volunteers are prepared, equipped with the necessary facilities as well as functional equipment, and readily on-call in the event natural disaster occurs as perceived by all groups of respondents.